Inosine: A broad-spectrum anti-inflammatory against SARS-CoV-2 infection-induced acute lung injury via suppressing TBK1 phosphorylation - Ningning Wang; Entao Li; Huifang Deng; Lanxin Yue; Lei Zhou; Rina Su; Baokun He; Chengcai Lai; Gaofu Li; Yuwei Gao; Wei Zhou; Yue Gao (Elsevier, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-induced cytokine storms constitute the primary cause of coronavirus disease 19 (COVID-19) progression, severity, criticality, and death. Glucocorticoid and anti-cytokine therapies are frequently administered to treat COVID-19, but have limited clinical efficacy in severe and critical cases. Nevertheless, the weaknesses of these treatment modalities have prompted the development of anti-inflammatory therapy against this infection. We found that the broad-spectrum anti-inflammatory agent inosine downregulated proinflammatory interleukin (IL)-6, upregulated anti-inflammatory IL-10, and ameliorated acute inflammatory lung injury caused by multiple infectious agents. Inosine significantly improved survival in mice infected with SARS-CoV-2. It indirectly impeded TANK-binding kinase 1 (TBK1) phosphorylation by binding stimulator of interferon genes (STING) and glycogen synthase kinase-3β (GSK3β), inhibited the activation and nuclear translocation of the downstream transcription factors interferon regulatory factor (IRF3) and nuclear factor kappa B (NF-κB), and downregulated IL-6 in the sera and lung tissues of mice infected with lipopolysaccharide (LPS), H1N1, or SARS-CoV-2. Thus, inosine administration is feasible for clinical anti-inflammatory therapy against severe and critical COVID-19. Moreover, targeting TBK1 is a promising strategy for inhibiting cytokine storms and mitigating acute inflammatory lung injury induced by SARS-CoV-2 and other infectious agents.